PERANCANGAN SISTEM CHARGING PADA BATERAI PURWARUPA MOBIL LISTRIK - Rivaldi Juswan; Tejo Sukmadi; Enda Wista Sinuraya (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
In the process of charging the battery, it is necessary to pay attention to the value of the current and voltage flowing to the battery. Currently, the battery is an essential tool for humans. Rechargeable battery technology is also increasingly helping meet human needs. The process of charging a rechargeable battery is carried out by flowing current continuously until the battery voltage increases to a certain value because overcharging can damage the battery so that the battery cannot last long. Charging time and battery life are highly dependent on the nature of the accumulator charger circuit. Incompatible currents and voltages can damage the battery and reduce battery life. This problem can be overcome by using a circuit breaker voltage and current. The charging method used is constant voltage, the cut-off circuit selection using a transistor as a voltage and current breaker has the advantage of being able to cut the voltage and current as limited without the need to replace components. Based on the test results, the cut off circuit can cut off the output voltage and current as limited. Based on the measurement results, the cut off circuit is able to cut off the voltage and current at a voltage of 13.43 V and a current of 0.97 A on a 65 Ah battery.